Intervalos intrajornadas - Fontana, Márcia Eliane (2009)
The study object of the current work is the intervals of intra-day s work under the Brazilian labor law. An analysis on intervals is carried out with the purposes of having harmony between the force spent by worker and the results desired by employer, taking always into account the intervention by the State in order to grant the accomplishment of constitutional rights and, therefore, to protect worker s health. The approach method to be adopted herein shall be inductive in view of the fact it advances from particular to general grounds. The research to be developed shall be bibliographical. It shall be highlighted that the employee s mental and physical recovery is the purpose of the interval of the intra-day s work. Hence, it is understood that the interval of the intra-day s work is deemed to be condition of hygiene, health and safety to the employee, which is guaranteed by rules of public policy nature (article 71 of CLT Brazilian Labor Act - and article 7th, XXII, of the CF/88 1988 Brazilian Federal Constitution) and contrary to collective agreement